A new method for empirical force field calculations on localized and delocalized carbocations - Clark, Timothy; Schleyer, Paul; et al. (Journal of Computational Chemistry, 1996)
A new empirical force field method for localized and delocalized carbocations is described. Additional geometry parameters for carbocations were added to Allinger's MMP2 molecular mechanics program, which can treat delocalized pi-systems. The effect of hyperconjugation in carbocations is introduced via a quantum chemical term into force field calculations for the first time. The calculated heats of formation are in excellent agreement with a wide range of experimental data; the largest deviations are about 3.5 kcal/mol. The calculated structures agree very well with those computed at correlated ab initio levels (MP2(full)/6-31G*). The relative energies and geometries of different conformations of representative carbocations also were in good agreement with MP4/6-31G*//MP2(full)/6-31G* results. (C) 1996 by John Wiley & Sons, Inc.